2022
DOI: 10.3390/polym14081618
|View full text |Cite
|
Sign up to set email alerts
|

Cold Plasma-Based Fabrication and Characterization of Active Films Containing Different Types of Myristica fragrans Essential Oil Emulsion

Abstract: Myristica fragrans essential oil (MFEO) is a potential active compound for application as an active packaging material. A new approach was developed using a cold plasma treatment to incorporate MFEO to improve the optical, physical, and bacterial inhibition properties of the film. The MFEO was added as coarse emulsion (CE), nanoemulsion (NE), and Pickering emulsion (PE) at different concentrations. The PE significantly affected (p < 0.05) the optical, physical, and chemical properties compared with CE and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Coating involves applying the emulsion to the substrate using a brush, roller, or sprayer and drying it to form a solid film. This method enables the creation of double‐layered films with different wall materials to protect active ingredients from volatility, oxidation, light, and thermal decomposition (Yudhistira et al., 2022). Another coating method is to immerse food in a solution and then dry it.…”
Section: Preparation Methods For Pefcmentioning
confidence: 99%
See 1 more Smart Citation
“…Coating involves applying the emulsion to the substrate using a brush, roller, or sprayer and drying it to form a solid film. This method enables the creation of double‐layered films with different wall materials to protect active ingredients from volatility, oxidation, light, and thermal decomposition (Yudhistira et al., 2022). Another coating method is to immerse food in a solution and then dry it.…”
Section: Preparation Methods For Pefcmentioning
confidence: 99%
“…Adding the emulsion to green degradable food packaging materials could help form a film‐forming liquid with good dispersity and strong stability, and it could be finally applied to food preservation by drying (solidifying the emulsion). Compared to nanoemulsion‐based films, PE‐based films have excellent release and control properties to enhance the stability of the functional properties of the packaging and extend the shelf life of the food (Yudhistira et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [ 79 ] described better-ordered porous structure and enhanced compatibility between zein and coating materials, while Chen et al [ 47 ] reported ordering of zein molecule secondary structure after plasma treatment. Cold plasma treatment, in general, were carried out by a few researchers including Yudhistira et al [ 73 ], Cui et al [ 76 ] and Lin et al [ 81 ]. The major effects on composite properties reported by them include improved coating adhesion, controlled release of active agents and surface modification for enhanced antimicrobial activity.…”
Section: Plasma Technology In Food Packagingmentioning
confidence: 99%
“…Such micro-nano roughness offers the entrapment of more micro air pockets and a high contact angle for water droplets. Ultimately, this provides the desired level of hydrophobicity [42][43][44][45]. Additionally, these flexible connections between nanofibers are suitable for enhancing the mechanical stability of the nonwoven materials [46].…”
Section: Morphological and Compositional Characterizationmentioning
confidence: 99%